Aparência, essência e exploração nas seções I e II do livro III de O Capital - Chagas, Eduardo Ferreira; Gonçalves, Mailson Bruno de Queiroz Carneiro (Kairós: Revista Acadêmica da Prainha, 2021)
The aim here is to demonstrate the association between appearance, essence and exploitation that underlies the surface of the capitalist economy. The process of infinite accumulation, as manifested in the sphere of competition, corresponds to a mystification of itself, since the cost price, that is, the sum necessary for the acquisition of the productive elements, is capable of generating value. The existence of surplus labor is absolutely camouflaged by the metamorphosis of the commodity, supposedly rooted in the intimate relationship between freedom and equality. The illusion has a particular purpose in denying wage labor as the foundation of a system marked by plunder, so that the dispute between singular capitals for control of the world market represents the development of the contradictions that transform wealth and misery into an indivisible totality.